Physiology and pathophysiology of cough - Pavord, I (Oxford University Press, 2012)
All pulmonary and many non-pulmonary conditions can present with a cough. Most will be evident after a simple clinical assessment that includes a history, physical examination, a chest radiograph, and a spirogram. A cough that remains unexplained after such an assessment is a common reason for referral to secondary care. Potential causes include asthma, eosinophilic bronchitis, rhinitis and gastro-oesophageal reflux. This chapter discusses the cough reflex, clinical aspects of chronic cough, treatment of chronic cough, cough in malignancy and palliative care, and cough in children.